Factors Associated with COVID-19 Infection of Survivors at Dr. Kariadi Hospital Semarang - Joko Wiyanto; Arip Susianto; Nanang Qosim; Sri Listyaning Wulan; Hikmi Muharromah Pratiwi; Amin Husni; Retnaningsih Retnaningsih (Universitas Muhammadiyah Semarang, 2022)
The transmission of COVID-19 infection is rapidly spreading in Indonesia, All people are at risk of COVID-19 infection, especially health workers. Factors that may increase the risk of COVID-19 transmission necessitate being explored more. This study aims to find out what factors are associated with the incidence of COVID-19 infection in COVID-19 survivors at Kariadi Hospital Semarang. This study has used a retrospective observational design, with a quantitative analysis conducted involving 80 COVID-19 survivors (health workers = 63 respondents, non-health workers = 17 respondents). Respondents' characteristics questionnaire, exposure questionnaires and knowledge, attitude and practice questionnaires were filled out by respondents through google form and then were analyzed by chi-square test. Most of the COVID-19 survivors in this study were male (52.5%), had a bachelor's degree (50%), married (77.5%), had no comorbidities (73.5%), had a high level of knowledge (90%), appropriate attitude (90%), and good preventive practice (95%), and the most common symptom of COVID-19 experienced was fever (15, 95%). The incidence of COVID-19 infection was significantly more in health worker survivors which were male (p = 0.032), as civil servants (ASN) (p = 0.00), had undergraduate education level (p = 0.00) and hospitalized during COVID-19 infection (p = 0.002). Factors related to the incidence of COVID-19 infection in this study were gender, occupation, education level, and hospitalisation place. Adequate screening and mitigation of COVID-19 risk groups are urgently needed.